Design, synthesis and biological evaluation of anti-pancreatic cancer activity of plinabulin derivatives based on the co-crystal structure. Issue 8 (1st May 2018) - Fu, Zhangyu; Hou, Yingwei; Ji, Cunpeng; Ma, Mingxu; Tian, Zhenhua; Deng, Mengyan; Zhong, Lili; Chu, Yanyan; Li, Wenbao
Graphical abstract: Highlights: Co-crystal structure guided rational design. Novel compounds with higher activity against human BxPC-3 cell line. Interaction explained by molecular docking studies. Abstract: Based on the co-crystal structures of tubulin with plinabulin and Compound 1 (a derivative of plinabulin), a total of 18 novel plinabulin derivatives were designed and synthesized. Their biological activities were evaluated against human pancreatic cancer BxPC-3 cell lines. Two novel Compounds 13d and 13e exhibited potent activities with IC50 at 1.56 and 1.72 nM, respectively. The tubulin polymerization assay indicated that these derivatives could inhibit microtubule polymerization. Furthermore, the interaction between tubulin and these compounds were elucidated by molecular docking. The binding modes of Compounds 13d and 13e were similar to the co-crystal structure of Compound 1 . H-π interaction was observed between the aromatic hydrogen of thiophene moiety with Phe20, which could enhance their binding affinities.